Komunikasi Antar Pribadi Ibu Kepada Anak (Studi Deskriptif Kualitatif Komunikasi Ibu Kepada Anaknya yang Disekolahkan di Pondok Pesantren dalam Membangun Motivasi Belajar Anak ) - HERLIYANAWATI, DIYAH; , Palupi, MA (2017)
The communication given by the mother on the child will determine the quality of the child. The intimacy and communication between children and mother is the key to the success of education in the family. Therefore, parents have to motivate children to success. Boarding is one of the educational institutions that offer mastery of science and religion at once. Boarding schools as institutions with the hope of getting a superior education in the field of both religious and academic so that the children become a human character, moralist, intellectual. Living in boarding schools, children are required to be away from his mother. Living in a different places makes the communication of mother be reduced. The purpose of this research is to find out how interpersonal communication mother with children who live in boarding in building children's learning motivation. This research used the interview as a data collection technique. The three informants in this research are a father or a mother who send his son in Modern Assalam boarding schools, Al Mu'min Ngruki boarding schools, and Al Muayyad boarding schools. The result of this research are the parents building children's learning motivation by encouraging children to have a high curiosity. Mother encourage children to learn to reach high achievement by giving support and building confidence in children so that the children want to do it seriously. Mother also encourage children to learn by providing prizes, praise as one of appreciation when children succeed in the learning process. Besides, parents do not give a punishment when children fail.